Implikasi Keberadaan Spesies Invasif Eceng Gondok Terhadap Komunitas Srangga Herbivor - Sapdi Sapdi (Jurnal Agrista, 2008)
Implication of the Existance of Invasive Species-Water Hyacinth on Communities of Herbivorous InsectABSTRACT. The introduction of an invasive exotic plant species may indirectly influence herbivorous insects community. The objective of the research is to evaluate the implication of the existence of invasive species-water hyacinth on herbivorous insect community. The research was done in several freshwater ecosystems occupied by water hyacinth in West Java and DKI Jakarta, conducted during January 2004 to March 2006. Sweep net and yellow pan trap were used to collect the sample of insects. The result of the research showed that the existence of water hyacinth may indirectly resulted in decreasing of species richness and diversity of herbivorous insect. The observation also showed that the existence of water hyacinth may lead to homogenezation of the insect in aquatic vegetation.